An innovative additively manufactured implant for mandibular injuries: Design and preparation processes based on simulation model - Zheng, Lingling; Wang, Chao; Hu, Min; Apicella, Antonio; Wang, Lizhen; Zhang, Ming; Fan, Yubo (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: For mandibular injury, how to utilize 3D implants with novel structures to promote the reconstruction of large mandibular bone defect is the major focus of clinical and basic research. This study proposed a novel 3D titanium lattice-like implant based on biomechanical and mechanobiological approach to optimize the implant tailored to specific patient biomechanical, physiological and clinical requirements. Methods: This objective has been achieved by matching and assembling different morphologies of a lattice-like implant mimicking cancellous and cortical bone morphologies and properties, namely, an internal spongy trabecular-like structure that can host bone graft materials and an external grid-like structure that can ensure the mechanical bearing capacity. Finite element analysis has been applied to evaluate the stress/strain distribution of the implant and bone graft materials under physiological loading conditions to determine whether and where the implant needs to be optimized. A topological optimization approach was employed to improve biomechanical and mechanobiological properties by adjusting the overall/local structural design of the implant. Results: The computational results demonstrated that, on average, values of the maximum von-Mises stress in the implant model nodes could be decreased by 43.14% and that the percentage of optimal physiological strains in the bone graft materials can be increased from 35.79 to 93.36% since early regeneration stages. Metal additive manufacturing technology was adopted to prepare the 3D lattice-like implant to verify its feasibility for fabrication. Following the approach proposed in this study, the well-designed customized implants have both excellent biomechanical and mechanobiological properties, avoiding mechanical failure and providing sufficient biomechanical stimuli to promote new bone regeneration. Conclusion: This study is expected to provide a scientific and feasible clinical bases for repairing large injuries of mandibular bone defects by offering new insights into design criteria for regenerative implants.